Profiling students’ misconception and concept mastery of the human body system topic - P S Melati; L Rusyati (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
Conceptual understanding is one of the important indicators to achieve the goals of science teaching and learning. Learning and teaching science will always be correlated with concepts. Students’ perception of science concepts is constructed from knowledge along the learning process. In science teaching-learning, misunderstanding and misconceptions of science are influencing the performance of middle and high school students. Before doing some remediation for misconception, the important things that teacher must be done is identify the students’ misconception. This research’s purposes are identifying the common misconceptions and alternative ideas of science education, and identifying students’ concept mastery of the topic. The instrument consisted of test items and one open-ended question related to the topic also modify with four tier test. Each student’s score is being averaged, the research found that the averages percentage of students’ scores is the same with the percentage of the correct answer. Based on these conditions it is very important to do improvement by carrying out more challenging learning and inviting students to construct new knowledge through the appropriate learning experience